Neuroinflammation, Microglia and Implications for Retinal Ganglion Cell Survival and Axon Regeneration in Traumatic Optic Neuropathy - Au, Ngan Pan Bennett; Ma, Chi Him Eddie (Frontiers in Immunology, 2022)
Traumatic optic neuropathy (TON) refers to a pathological condition caused by a direct or indirect insult to the optic nerves, which often leads to a partial or permanent vision deficit due to the massive loss of retinal ganglion cells (RGCs) and their axonal fibers. Retinal microglia are immune-competent cells residing in the retina. In rodent models of optic nerve crush (ONC) injury, resident retinal microglia gradually become activated, form end-to-end alignments in the vicinity of degenerating RGC axons, and actively internalized them. Some activated microglia adopt an amoeboid morphology that engulf dying RGCs after ONC. In the injured optic nerve, the activated microglia contribute to the myelin debris clearance at the lesion site. However, phagocytic capacity of resident retinal microglia is extremely poor and therefore the clearance of cellular and myelin debris is largely ineffective. The presence of growth-inhibitory myelin debris and glial scar formed by reactive astrocytes inhibit the regeneration of RGC axons, which accounts for the poor visual function recovery in patients with TON. In this Review, we summarize the current understanding of resident retinal microglia in RGC survival and axon regeneration after ONC. Resident retinal microglia play a key role in facilitating Wallerian degeneration and the subsequent axon regeneration after ONC. However, they are also responsible for producing pro-inflammatory cytokines, chemokines, and reactive oxygen species that possess neurotoxic effects on RGCs. Intraocular inflammation triggers a massive influx of blood-borne myeloid cells which produce oncomodulin to promote RGC survival and axon regeneration. However, intraocular inflammation induces chronic neuroinflammation which exacerbates secondary tissue damages and limits visual function recovery after ONC. Activated retinal microglia is required for the proliferation of oligodendrocyte precursor cells (OPCs); however, sustained activation of retinal microglia suppress the differentiation of OPCs into mature oligodendrocytes for remyelination after injury. Collectively, controlled activation of retinal microglia and infiltrating myeloid cells facilitate axon regeneration and nerve repair. Recent advance in single-cell RNA-sequencing and identification of microglia-specific markers could improve our understanding on microglial biology and to facilitate the development of novel therapeutic strategies aiming to switch resident retinal microglia’s phenotype to foster neuroprotection.